P-25 Advance care plans and not for resuscitation orders: A multi site audit and review across five australian hospitals. (1st September 2015) - Mills, A; Levinson, M; Hutchinson, AM; Walker, Amanda; Stephenson, G; Gellie, A; Heriot, G; Newnham, H; Robertson, M
Abstract : Background: Australian hospitals mandate the provision of in hospital CPR, in the absence of treatment limiting documentation. Aim: To determine (a) barriers to the writing of and (b) the prevalence of treatment limiting orders. Methods: A point prevalence review of patient medical records, and a qualitative review of hospital policy and documentation, across five hospitals. Results: Of 1934 patient records reviewed (547 aged >80 years), 15 advance care plans and 230 not for resuscitation orders were identified. Orders were written for a further quarter of patients receiving a medical emergency team call. A lack of standardisation in documentation was evident across health services, where each site used its own unique form and accompanying policies. Differences were found in who could authorise the decision, what was included on the form, the role of patients and families, and how discussions were managed and dissent resolved. Futility and burden of treatment were not defined independently of each other. Discussion: Given the proportion of patients aged 80 years and over, fewer limitations of treatment orders were found than might be expected. Inconsistencies across sites contributed to a lack of clarity regarding decisions to withhold resuscitation. We have developed a two stage process of documentation, to firstly facilitate discussion of patient specific goals of care, and then secondly to consider and implement limitation of treatment orders. Conclusion: Decisions to withhold resuscitation are innately complex but could be aided by separating the decision making process from the communication of the decision, resulting in improved end of life care.